Exercise, nutrition, and aging in the regulation of muscle protein synthesis - Koji Sato; Satoshi Fujita (Journal of Physical Fitness and Sports Medicine, 2013)
Sarcopenia is the age-associated loss of skeletal muscle mass and strength that develops slowly over decades and becomes a significant factor to disability among the elderly population. Recent studies have indicated that blunted anabolic response to nutritional stimuli significantly contributes to the development of sarcopenia. In the present article, we will review recent findings on the role of nutritional intake on muscle protein metabolism in the elderly. This review will particularly focus on acute anabolic responses to amino acids and protein intake, age-associated changes in the response of muscle protein to meal intake, and the role of insulin resistance in muscle protein metabolism. The relationship between age-associated decline of sex steroid hormones and muscle anabolism will also be discussed in addition to the benefits of resistance exercise in muscle protein anabolism. Additionally, recent evidence on the time-course of anabolic response, molecular regulation of muscle protein synthesis, and long-term training effects will be discussed. Finally, recent evidence on the cumulative effect of resistance exercise in combination with nutritional supplementation on muscle protein metabolism will be discussed to propose possible preventative measures against sarcopenia.